Análise da turbulência nas correntes de densidade em configuração lock-release - Sosa, Sara María Mata (2023)
Density currents are flows driven by density differences between the current and the ambiente fluid. When the density difference is due to particles in suspension, the current is called turbidity current, with particle concentration. These particles are characterized by the settling velocity (us). At the interface between the current and the ambiente fluid, a mixing zone develops, where complex structures are generated by the interaction of shear, buoyancy and turbulence, triggering processes such as entrainment and mixing. The quantity that characterizes turbulence is the Reynolds number (Re). Re density currents in O(Re4) are considered turbulent. In this study, density currents are simulated for Re = 3450, 8950 and 15000, and turbidity currents of Re = 8950 with concentration of mono-disperse particles of us = 0.006, 0.0125 and 0.029, in the lock-release configuration, using Direct Numerical Simulation and Implicit Large Scale Simulation. The high-order solver Xcompact3d is used to solve the Navier-Stokes and scalar transport equations, in the Boussinesq approximation on a Cartesian grid. The current dynamics propagation is characterized through global magnitudes; front position (xf ), front velocity(uf ), concentration (φhc) and head height hc of the density current, finding power laws of uf and hc in function us. The statistical approach of Reynolds decomposition is applied to calculate velocity and concentration fluctuations, for slumping, inertial and viscous regimes. The turbulent kinetic energy balance (KTE) and the scalar variance (SV) are studied for all simulation times, finding trends that characterize the dynamic regimes of the density currents propagation. Turbulent structures were characterized using the Q-criterion. The relationship of turbulent structures with KTE and SV was verified, concluding that maximum values are obtained with the vortices break-down into smaller structures, in the final times of the slumping regime.